Corporate giving in Taiwan: agency cost theory vs. value enhancement theory. Issue 1 (1st January 2017) - Lin, Chien-Pang; Chen, Ming-Hsiang; Wang, Jie; Tian, Li
Abstract: This article examines the determinants of corporate giving ( CG ) in Taiwan according to agency cost (AC) and value enhancement (VE) theories. Panel regression test results reveal several new and interesting pieces of evidence. First, VE determinants outweigh AC determinants in explaining CG there. Second, the positive link between the current CG ratio ( CGR ) and the lagged CGR ( CGR (-1)) suggests the consistent nature of CG . Third, after the global financial crisis in 2008, the influence of debt leverage on CGR vanished, but the impact of managerial insiders' shareholdings on CGR became significant. Last, the influences of VE determinants and CGR (-1) on CGR remain during both pre-crisis and post-crisis periods. Moreover, after the crisis, CG was still motivated to create current value for shareholders, and was apparently used as a business strategy to signal companies' financial or managerial stability.